Proper management of inoperable malignant hilar biliary obstruction: Endoscopic retrograde cholangiopancreatography, endoscopic ultrasound, or percutaneous approach? - Tae Hoon Lee (Society of Gastrointestinal Intervention, 2021)
Advanced malignant hilar biliary obstrucion (HBO) is commonly caused by hilar cholangiocarcinoma, gallbladder cancer, hepatocelluar carcinoma, or metastatic tumors. Although surgical resection is the only curative treatment, the majority of patients can not undergo surgery due to an advanced inoperable state upon presentation. Therefore, effective biliary drainage is currently the mainstay palliative treatment for symptomatic improvement of HBO. Percutaneous access has been preferred traditionally, especially for advanced HBO because of technical difficulty involved. Recently, primary endoscopic palliation using plastic or metal stents has shown higher technical feasibility and clinical success without increasing the risk of adverse events compared to percutaneous access, even for high-degree HBO. Endoscopic ultrasound (EUS)-guided intervention has also been introduced for primary cases having a failed endoscopy or surgically altered anatomy and for reintervention. However, primary approach methods such as percutaneous, endoscopic retrograde cholangiopancreatography, and EUS have numerous issues involving the use of stents, including the type of stents, the number of stents, the deployment method, and additional efficacy of local therapies. This review describes current effective biliary drainage methods for advanced inoperable HBO based on reported studies.